Safety and efficacy of navitoclax, a BCL-2 and BCL-XL inhibitor, in patients with relapsed or refractory lymphoid malignancies: results from a phase 2a study. Issue 4 (21st March 2021) - de Vos, Sven; Leonard, John P.; Friedberg, Jonathan W.; Zain, Jasmine; Dunleavy, Kieron; Humerickhouse, Rod; Hayslip, John; Pesko, John; Wilson, Wyndham H.
Abstract: Navitoclax, a novel BCL-2 and BCL-XL inhibitor, demonstrated promising antitumor activity in the dose-escalation part of a phase 1/2a study (NCT00406809) in lymphoid tumors. Herein, we report the continued safety and efficacy results of the phase 2a portion. Twenty-six adult patients with relapsed/refractory follicular lymphoma ( n = 11, Arm A) and other relapsed/refractory lymphoid malignancies ( n = 15, Arm B) were enrolled. Navitoclax administration schedule consisted of a 150-mg 7-day lead-in dose followed by 250-mg daily dosing with the option to further increase to 325 mg after 14 days if the 250-mg dose was tolerated. All patients experienced at least 1 treatment-related adverse event (TRAE). Seventeen (65.4%) patients reported grade 3/4 TRAEs; thrombocytopenia (38.5%) and neutropenia (30.8%) were the most common. Two patients reported serious AEs; none were fatal (no deaths occurred within 30 days of last dose of study drug). The objective response rate (complete and partial) was 23.1% (6/26; Arm A: 9.1%, Arm B: 33.3%). Median progression-free survival and time to progression were identical: 4.9 months (95% CI: 3.0, 8.2); median overall survival: 24.8 months (95% CI could not be computed). Navitoclax monotherapy has an acceptable safety profile and meaningful clinical activity in a minority of patients with relapsed/refractory lymphoid malignancies.